2016
DOI: 10.5194/amt-9-5423-2016
|View full text |Cite
|
Sign up to set email alerts
|

The operational methane retrieval algorithm for TROPOMI

Abstract: Abstract. This work presents the operational methane retrieval algorithm for the Sentinel 5 Precursor (S5P) satellite and its performance tested on realistic ensembles of simulated measurements. The target product is the columnaveraged dry air volume mixing ratio of methane (XCH 4 ), which will be retrieved simultaneously with scattering properties of the atmosphere. The algorithm attempts to fit spectra observed by the shortwave and near-infrared channels of the TROPOspheric Monitoring Instrument (TROPOMI) sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
128
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 52 publications
4
128
0
Order By: Relevance
“…The retrieval success rate (ratio between the number of successful retrievals and the number of attempted retrievals) is taken to be 5 3% for SWIR (Hu et al, 2016) and 60% for TIR (Xiong et al, 2008) because SWIR observations require cloud-free pixels whereas TIR has tolerance for fractional cloud cover. The retrievals are for the dry air column mixing ratio X [ppb] after applying typical averaging kernels to describe vertical sensitivity (Figure 3).…”
Section: Synthetic Observationsmentioning
confidence: 99%
“…The retrieval success rate (ratio between the number of successful retrievals and the number of attempted retrievals) is taken to be 5 3% for SWIR (Hu et al, 2016) and 60% for TIR (Xiong et al, 2008) because SWIR observations require cloud-free pixels whereas TIR has tolerance for fractional cloud cover. The retrievals are for the dry air column mixing ratio X [ppb] after applying typical averaging kernels to describe vertical sensitivity (Figure 3).…”
Section: Synthetic Observationsmentioning
confidence: 99%
“…To separate the sources/sinks of CO 2 and CH 4 from variations of surface pressure and specific humidity, the abundances of CO 2 and CH 4 are usually represented by the column‐averaged dry mole fractions ( normalXCO2 and normalXCH4). To sufficiently constrain their distributions and trends through inverse modeling, normalXCO2 has to be retrieved to a precision of 0.25–0.5% (1–2 ppmv; Crisp, ; Frankenberg et al, ; Miller et al, ), and normalXCH4 has to be retrieved to a precision of better than 1% (20 ppbv; Bergamaschi et al, , ; Hu et al, ) without significant geographically varying biases.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations have shown that in particular the methane retrieval is very sensitive to errors in the instrument spectral response function (ISRF or instrument line shape). As a result, the requirement on the ISRF is formulated that it should be known with an accuracy of 1 % of its maximum where the ISRF is greater than 1 % of its maximum (Hu et al, 2016). To reach the required accuracy, data have been measured with high spectral resolution using a scanning monochromatic light source covering the SWIR band.…”
Section: Introductionmentioning
confidence: 99%